Dampak Stock Split terhadap Abnormal Return pada Emiten Terdaftar di Bursa Efek Indonesia - Achmad Azis Fauzi; Ali Mutasowifin (JDEP (Jurnal Dinamika Ekonomi Pembangunan), 2021)
This study analyzes the effect of stock split on abnormal returns of companies listed on the Indonesia Stock Exchange in 2015-2019. Using a purposive sampling method (nonprobability sampling) we obtained 34 companies as a research sample. We use the event study approach for data processing in finding abnormal returns and t-test as well. This study classifies samples into two categories, complex sample category, and sectoral industries. The result shows that for the complex category, there are three out of eleven days of events that have an impact on abnormal returns marked by the t-test results greater than t-table. Whereas in each sectoral industries there are only five affected sectors, three unaffected sectors and one sector cannot be tested due to insufficient data. This result is also consistent with theories related to the stock split, signaling theory, and trading range theory.